Fé, tradição e cultura no lugar: a festa de Santa Maria Madalena em União dos Palmares – Alagoas - Belo, Carlos (2017)
The religious parties are spacial and temporal phenomenons which provide a geographical and cultural comprehension of the places where they occur. It constitutes a meaningfully explored theme in the human and social sciences and it has been gaining expressivity in Geography across the Geography of Religion that turns to the spacial-temporal analysis of theses events that produce in the space its marks, establishing, this way, it‟s own spacial dimension, besides becoming an identity brand from the places where they occur. Following this perspective, we aim in this work, which is the product of a Master‟s research still in process, analyse the Santa Maria Madalena‟s party, patronesse of the city of União dos Palmares, located in the mesoregion of the Alagoan east, that happens since 1835, when the parish dedicated to her was created. So, constituting a tradition of more than 180 years of history. Methodologically the research is anchored in the propositions of Rosendahl (2012), based on the assumption that the studies which involve the relationship between the sacred and the profane in light of a geographic analysis are scheduled in three dimensions: (1) the dimension of the place, (2) the economic dimension and (3) the politic dimension. From these three dimensions is possible to understand, for example, the symbolic goods present in the party, as well as the exercise of the theocratic power in its actions of territoriality. Indeed, the place composes part of the geographic analysis in the comprehension of the relationship of man with the space. In turn, the economic dimension is ruled in the material and symbolic goodies that represent the sacred and the profane, whose process of production occurs in the space and time. Regarding to the politic dimension, it is observed that the agents who administer the sacred controll the production of the goodies and symbolic services that composes it. The religious money turns an instrument of power to the manutention of the religious practice. Moreover, it should be considered that the act of celebrating is also a way of conserving something that take place in the coletive memory, specially when it is relationed to the devotional act to the saint. It‟s this way that the maintenance of the Santa Maria Madalena‟s party is shared for the politic action of the Catholic Church and for many people from differents sectors of the local society and even from the adjacencies, who carry a common identity, a feeling that integrates the religious comunity during the festivities yearly realized, culminating with the procession, traditionally realized in the second day of february. Therefore, printing a strong relationship with the palmarin territory, confering to it specificities of cultural, politic, economic nature and, consequently, territorial identity.